Noise source identification of diesel engine based on variational mode decomposition and robust independent component analysis. (15th January 2017) - Yao, Jiachi; Xiang, Yang; Qian, Sichong; Wang, Shuai; Wu, Shaowei
Highlights: The lead wrapped method was adopted to isolate the No. 1–5 cylinders, only the No. 6 cylinder part was bared. In order to eliminate the aerodynamic noise, the exhaust main of diesel engine was connected to the outdoor by a long pipe. The diesel engine drag test was carried out, so that the piston slap noise can be measured separately. It can be used for comparison with separated results. The VMD-RobustICA-CWT method is proposed to separate and identify the noise sources of the 6-cylinder diesel engine. The results show that the VMD-RobustICA-CWT method has better performance than the EEMD-RobustICA-CWT method. Abstract: Through separating and identifying the noise sources of diesel engine, each independent noise obtained can be used as reference for the noise reduction, condition monitoring and fault diagnosis. In the noise source identification of diesel engine, the combustion noise and the piston slap noise are found to be overlapped in time domain and frequency domain. So it is intricate to accurately separate them. Therefore, the noise source identification method which is based on variational mode decomposition (VMD), robust independent component analysis (RobustICA) and continuous wavelet transform (CWT) is proposed. In the test, a 6-cylinder diesel engine was tested in a semi-anechoic chamber. The lead wrapped method was adopted to wrap No. 1–5 cylinders so as to isolate the interference noises, only the No. 6 cylinder part was bared. The single channel noise signal of cylinder head was measured. Then the variational mode decomposition algorithm is utilized to decompose the noise signal into several variational mode components. The RobustICA algorithm is adopted to extract the independent components. Finally, the continuous wavelet transform and the prior knowledge of diesel engine are applied to further identify the separated results. The results show that by using the proposed method to separate and identify the radiation noise of the cylinder head of the diesel engine, the independent components obtained are respectively the combustion noise and the piston slap noise. Comparing with the EEMD-RobustICA-CWT method, each independent noises obtained through the proposed method are more accurate and pure with less other interference noises.